Un caso de poliginia en el Halconcito Colorado (Falco sparverius) - De Lucca, Eduardo R. (1993)
In this paper we describe a case of poliginy in the American Kestrel (Falca spatverius). Two females had their nests within the territory of a male. The male copulated with the two females and defended their territory against intruders. The male played the usual male role with one female (primary) but never was seen feeding the other one (secondary). Secondary female managed to go through incubation and part of the nestling period (at least up to day 10 of nestling's life) without the aid of the male.